COVID‐19 in lung transplant recipients. Issue 6 (22nd July 2020) - Myers, Catherine N.; Scott, John Harwood; Criner, Gerard J.; Cordova, Francis C.; Mamary, Albert James; Marchetti, Nathaniel; Shenoy, Kartik V.; Galli, Jonathan A.; Mulhall, Patrick D.; Brown, James C.; Shigemura, Norihisa; Sehgal, Sameep; et al.
Abstract: Solid organ transplant recipients are considered at high risk for COVID‐19 infection due to chronic immune suppression; little data currently exists on the manifestations and outcomes of COVID‐19 infection in lung transplant recipients. Here we report 8 cases of COVID‐19 identified in patients with a history of lung transplant. We describe the clinical course of disease as well as preexisting characteristics of these patients.